The problem of trust - Seligman, Adam B., 1954- (Princeton University Press, 1997)
The problem of trust in social relationships was central to the emergence of the modern form of civil society and much discussed by social and political philosophers of the early modern period. Over the past few years, in response to the profound changes associated with postmodernity, trust has returned to the attention of political scientists, sociologists, economists, and public policy analysts. In this sequel to his widely admired book, The Idea of Civil Society, Adam Seligman analyzes trust as a fundamental issue of our present social relationships. Setting his discussion in historical and intellectual context, Seligman asks whether trust--which many contemporary critics, from Robert Putnam through Francis Fukuyama, identify as essential in creating a cohesive society--can continue to serve this vital role.Seligman traverses a wide range of examples, from the minutiae of everyday manners to central problems of political and economic life, showing throughout how civility and trust are being displaced in contemporary life by new "external' system constraints inimical to the development of trust. Disturbingly, Seligman shows that trust is losing its unifying power precisely because the individual, long assumed to be the ultimate repository of rights and values, is being reduced to a sum of group identities and an abstract matrix of rules. The irony for Seligman is that, in becoming postmodern, we seem to be moving backward to a premodern condition in which group sanctions rather than trust are the basis of group life.